THE INVESTIGATION OF ONLINE EVALUATION IN TEACHING ENGLISH LANGUAGE (ResearchJet Journal of Analysis and Inventions, 2021)
This study expected to distinguish sorts of online evaluation carried out by English educators and to investigate the students' perception of utilizing on the web evaluation. The specialist gathered the information by survey, meet, and documentation. The specialist utilized procedure of investigating the information which have three stages. They are Data Reduction, Data Display, and Drawing Conclusion. For the reliability of the information, the specialist utilized Methodological Triangulation. The outcome showed that all English educators have executed variative online appraisal through Google Form, Google Classroom, Edmodo, Quizzes, and Instagram. There are benefits, detriments, challenges face by the educator applied online appraisal like planning the correct evaluation, controling the understudy in on the web, and got terrible web association. Then, the learners have positive and negative insight toward the execution of online evaluation. The positive insight showed that the understudy appreciated the online evaluation, acquired input quickly, adaptable, efficient, powerful, and more sure in doing on the web evaluation. Nonetheless, the understudy likewise had negative insight, for example, need web information, less inspiration, unfocussed, cheating, and need a more drawn out time